2012
DOI: 10.1186/1756-0500-5-371
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between the rs2294008 polymorphism in the prostate stem cell antigen gene and colorectal neoplasia: a case-control and immunohistochemical study

Abstract: BackgroundProstate stem cell antigen (PSCA) has been implicated in the pathogenesis of several solid tumours, either due to changes in protein expression, or through association with the rs2294008 polymorphism in the PSCA gene. To our knowledge, the role of PSCA in the development of colorectal neoplasia has not been explored. We performed a genotyping study to assess for associations between the rs2294008 polymorphism and risk of adenomatous polyps and colorectal cancer. DNA samples were available from 388 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…To date, there was only one attempt to associate rs2294008 polymorphisms of PSCA gene with CRC in European subjects. Smith and colleagues performed a study in 388 CRC patients and 496 controls and found no associations of this polymorphism and the risk of CRC (Smith et al, 2012). Our data support the findings of the later study, as rs2294008 and rs2976392 were not related with CRC development.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…To date, there was only one attempt to associate rs2294008 polymorphisms of PSCA gene with CRC in European subjects. Smith and colleagues performed a study in 388 CRC patients and 496 controls and found no associations of this polymorphism and the risk of CRC (Smith et al, 2012). Our data support the findings of the later study, as rs2294008 and rs2976392 were not related with CRC development.…”
Section: Discussionsupporting
confidence: 87%
“…Since different cancers may share common pathogenetic pathways (Bunney and Katan, 2006), we hypothesized that SNPs that have been implicated in other gastrointestinal carcinomas may also play a role in CRC development. To date, there are very few papers which have assessed this relationship in CRC patients (Li et al, 2012b;Smith et al, 2012;Wang et al, 2014). Furthermore, to our best knowledge this is the first report aimed at evaluating the role of rs4072037 and rs2274223 for CRC development in European population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequently, it has been demonstrated to be entailed in the pathogenesis of several neoplasms in a tissue/organ specific manner (Smith et al, 2012). PSCA, involving either change in protein expression or through association with the polymorphism in the PSCA gene, may act as an oncogene; play a role in tumor progression in some cancers while tumor suppressor gene in others (Saeki et al, 2010;Smith et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it has been demonstrated to be entailed in the pathogenesis of several neoplasms in a tissue/organ specific manner (Smith et al, 2012). PSCA, involving either change in protein expression or through association with the polymorphism in the PSCA gene, may act as an oncogene; play a role in tumor progression in some cancers while tumor suppressor gene in others (Saeki et al, 2010;Smith et al, 2012). Genetic variants of PSCA have been found to be strongly associated with the risk for cancers of the breast (Kim et al, 2012), bladder (Rothman et al, 2010), duodenal (Tanikawa et al, 2012) and stomach (Qiao and Feng, 2012) etc.…”
Section: Introductionmentioning
confidence: 99%